Revalidation of the ATTRACTION-4 study in a real-world setting: a multicenter, retrospective propensity score matching study in China - Dai, Yuhong; Liu, Yongqing; Gong, Zhimin; He, Lilin; Wang, Lei; Yang, Wenjie; Qiu, Ping; Zhang, Fangyuan; Yuan, Xianglin; Cheng, Henghui; Qiu, Hong (Frontiers in Immunology, 2023)
Background: Immune-checkpoint inhibitors (ICIs) combined with chemotherapy have been successfully used in clinical trials to treat advanced gastric cancer. However, the efficacy and safety of first-line immunotherapy combined with chemotherapy in Chinese patients are unknown. Methods: This multicenter retrospective study included patients with human epidermal growth factor receptor-2 (HER-2) negative advanced gastric cancer treated with first-line chemotherapy or chemotherapy with an ICI between January 2019 and December 2022. Propensity score matching was used to compare progression-free survival (PFS), overall survival, objective response rates, and adverse reactions between cohorts. After propensity score matching, 138 patients, who had balanced baseline characteristics, were included in the chemotherapy and combination treatment groups. The median follow-up duration was 16.90 months, and the median PFS was 8.53 months (95% confidence interval [CI] 7.77-9.28) in the combination treatment group and 5.97 months (95% CI 4.56-7.37) in the (PSM) 删除[Author]: